Modular nursing and patient and staff satisfaction at Davao Doctors Hospital - Pedres, Jenilee C.
The change towards an improved nursing care delivery system requires nursing leaders whose zest for attaining professionalism in the nursing practice is greater than the work required in implementing the change. Of equal importance is the openness and willingness of the staff to adapt the new norms, values, roles and responsibilities that the system brings.This scenario was observed when the nursing department of Davao Doctors Hospital took the challenge of improving their nursing care delivery system. The change was from the functional type of nursing care to the modular system.During the period of implementing this change, this study was done to determine the effect of modular nursing on patient and staff satisfaction utilizing the pretest-posttest research design. One hundred patients before and after one month of implementation of modular nursing responded to the Patient Satisfaction Questionnaires that were distributed before their discharge. There were 45 staff nurses who participated in this study when functional nursing was still utilized. One month after the implementation of the new system, 40 staff nurses participated in the study by answering the same Staff Satisfaction Questionnaire.The review of related literature and studies led to the development of a conceptual framework wherein an increase in patient and staff satisfaction is expected as a result of the closer nurse-patient relationship and the genuine direct care brought about by the modular system or modified primary nursing system.Quantitative results showed that the patients have not shown a significant increase in their Patient Satisfaction Mean Scores following the implementation of the Modular Nursing system. This might be explained by the variances of the two groups of patients. The unmatched patient groups on the other potentially relevant variables might have resulted on the negative results of the study. These unmeasured differences in the two groups of patients on other variables such as hospital days, number of times admitted, age and sex might be related to satisfaction. The nurses on the other hand showed a significant increase in their level of satisfaction after the implementation of the system.The qualitative data gathered also provided some significant information in relation to how the patients and staff viewed nursing care and the nursing system. Patients have identified more desirable aspects of nursing care in modular nursing. This difference in results may be because the open-ended questions enabled the patients to express themselves more. They may also had more one-to-one encounters with the nurses which allowed them to observe and experience being cared for by the nurses. The staff have also identified more patient-related advantages of the modular nursing system vis-a-vis the functional type.Future evaluation was recommended to the nursing administration. The tools used may also be expanded to include administrative and clinical items and other aspects of job satisfaction. Other nursing services in Davao City may also implement modular nursing for the benefits to be also experienced by them.